Keanekaragaman Cendawan dari Cairan Ecoenzyme dengan Sumber Bahan Organik Berbagai Jenis Kulit Jeruk - Ihdina Aurora Nurul Aulia; Dezi Handayani (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2022)
Ecoenzyme is a liquid from the fermentation of organic matter, sugar and water or commonly known as environmentally friendly enzymes. Ecoenzyme liquid contains various secondary metabolites produced by microbes (bacteria and fungi) that exist during the fermentation process. Ecoenzymes can generally be made from organic materials such as vegetable waste and unprocessed fruit waste. One of the organic materials that is easily obtained and produces ecoenzyme with a distinctive aroma is orange peel. The purpose of this study was to determine the types of fungi from ecoenzyme liquid with organic sources of various types of orange peel. This research is a descriptive research conducted in June-December 2021 at the Research Laboratory of the Biology Department, FMIPA UNP. The ecoenzyme samples used were a mixture of several types of citrus, namely honey orange peel, Mandarin orange, Pasaman orange, Gunung Omeh orange, lime and kaffir lime. The results showed that the ecoenzyme sample found 1 fungal isolate. The results of macroscopic and microscopic observations generally obtained that the fungal isolates were round with wavy edges, slow growth, brownish white in color, the cells were flat rod-shaped and quite long, had a rough surface, and had one nucleus. The isolates obtained showed the characteristics of yeast. Therefore, it can be concluded that it was successful to isolate 1 fungal isolate from ecoenzyme liquid with organic sources of various types of orange peels.